Sierra Leone : Joint Staff Assessment of the Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents the Joint Staff Assessment of Sierra Leone's Poverty Reduction Strategy Paper (PRSP) Preparation Status Report. Progress in the preparation of the PRSP has been slow. Consequently, the original completion date of end-December 2002 envisaged in the interim poverty reduction strategy paper (I-PRSP) was not attained, and the new target completion date is end-December 2003. The delay has been owing to the slow pace in implementing the disarmament exercise, the conduct of general elections, and administrative and financing difficulties.